TRADISI FESTIVAL PERAHU LAYAR "JONGKONG" DI KECAMATAN BURU KABUPATEN KARIMUN - Melay, M.Hum, Ridwan; ', Darmawan; ', Drs.Kamaruddin, M.Si (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Saling boats or jongkong is the one of folk game in the along the Karimun coastline and become a tradition for the Malay people that live as fisherman. Now a days this game (festival) is the annual event. This game always conducted to commemorate the independence day on seven teenth August. Aim of this research are to discover (1) history of sailing boat “jongkong” festival in the Buru Region, Karimun Regency. (2) the incentive factors of sailing boat “jongkong” festival in the Buru Region, Karimun Regency. (3) the shape and the parts of sailing boat “jongkong” in the Buru Region, Karimun Regency (4) the conduction process of the sailing boat “jongkong” festival game in the Buru Region, Karimun Regency. (5) the benefit for the citizen in the sailing boat “jongkong” festival game on Buru Region, Karimun Regency. Methods used in this research are historic methoods and qualitative methods. Data generated from interview result analyzed to the own language. The research location in the Buru Region, Karimun Regency. The research began from proposal colloquium to the scription examination. Data collection technics use the observation technic, interview technic, documentation technic, and literature study technic.Keywords: Tradition, Sailing Boat Festival